EFFECTS OF THIAMINE AND ASCORBIC ACID IN SEPTIC PATIENTS ADMITTED TO THE INTENSIVE CARE UNIT - Basheer Abdullah Abdelrahman; Muhammad Asim Rana; Ahmed Hossameldin Ahmed Awad; Ahmed M Abdelbaky; Wael Ghaly Elmasry; Mujtaba Hasan Siddiqui (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Thiamine and ascorbic acid have been increasingly studied for their potential benefits in treating septic patients in intensive care units (ICUs). This review brings together recent findings from databases such as PubMed, Scopus, Web of Science, and Google Scholar, focusing on studies published in the last ten years. These vitamins play critical roles in improving cell metabolism, reducing inflammation, and combating oxidative stress. Key findings include their impact on reducing organ damage, improving survival rates, and mitigating the severe effects of sepsis. Although initial studies are promising, more comprehensive research is required to confirm their effectiveness and establish standard treatment protocols. The review provides insights into the biochemical mechanisms, clinical applications, and future directions for incorporating these vitamins into routine sepsis care.